A horizon scan of music therapy in education - Lyu, Yifei; Wang, Xiangyu (Frontiers in Psychology, 2025)
IntroductionMusic therapy has gained increasing recognition for its benefits in educational settings, particularly in supporting students with diverse learning needs and promoting overall well-being. However, existing reviews reveal several limitations, including fragmented research efforts, limited interdisciplinary and international collaboration, and practical constraints such as insufficient funding and a shortage of trained music therapists. These gaps highlight the need for a more comprehensive understanding of the field’s development.MethodsThis research systematically examined publication trends, key contributors, and thematic clusters in the field of music therapy in education. Both quantitative indicators (e.g., publication and citation patterns) and qualitative thematic analysis were employed to generate an integrated overview of current research dynamics.ResultsThe analysis revealed a strong increase in publications and citations, largely driven by Western institutions. Despite this growth, several persistent challenges were identified: research fragmentation, limited international collaboration, and a notable underrepresentation of studies focusing on media-related aspects of music therapy.DiscussionThe study recommends strengthening interdisciplinary and international research networks, expanding investigations into media-related practices, developing standardized assessment tools, and increasing support in terms of funding and professional development. These recommendations provide a strategic roadmap for advancing music therapy in educational contexts and offer actionable guidance for researchers, educators, and policymakers aiming to enhance its integration and effectiveness.